Analisis Kepuasan Masyarakat Terhadap Program Sanitasi Total Berbasis Masyarakat Di Dusun Muntigunung, Desa Tianyar Barat, Kecamatan Kubu, Kabupaten Karangasem Tahun 2012 - Satyani, Happy Ari (Community Health, 2013)
Community-based Total Sanitation (STBM) program in Muntigunung carried out the pilot project in three group, Cangkeng, Kul-kul 1, and Kul-kul 2. The program goal is changing behavior of open defecation to collectively. The research purpose is measuring predispose factors for the community satisfaction and sustainability of STBM. The research design was cross sectional research with structured interview method. Samples were households of Cangkeng and Kul-kul 2. Data was analyzed using linear regretion method. The test was determines the correlation between variables such as facilitation, participation, and attitude toward the indicator of community satisfaction and program sustainability. The community satisfaction was measured by actual usage facility and the value of the STBM benefits among community. The facility actual usage of Cangkeng community was greater than Kul-kul 2 (82,6% and 52,9% respectively).There was high rate for the value of benefit variable in Cangkeng 65,2% and only 35,3% in Kul-kul. Linear regression analysis indicated that there was a significant relationship between facilitating and participation toward community satisfaction the program. The relationship facilitating and participation is Strong (R =0.741and R= 0.760). However relationships between benefit of value with program sustainability is weak (R =0.490). Results of linear equations showed that facilitating and participation coefficients (B) towards facility actual usage are0.318 and 0.291. The facilitating and participation coefficient (B) to the value of benefits are 0.535 and 0.462. Satisfaction and sustainability also showed significant correlation with the coefficient (B) was 0,135. The study can be concluded that community participation and facilitating should be increased in order improved the acceptance of STBM program in the community.
Keywords: STBM, Program Satisfaction, Program Sustainability